Inside job - Ferguson, Charles; Marrs, Audrey; Sony Pictures Classics (Firm). (London : Sony Pictures Home Entertainment, 2011)
Award-winning documentary analysing the global financial crisis of 2008, which plunged America and many other First World countries into recession. Based around interviews with politicians, journalists, academics and financial insiders, the film chronicles the rise of a largely unregulated financial services industry that eventually imploded, bringing the economy to its knees. The film is narrated by actor Matt Damon and won the 2011 Academy Award for Best Documentary Feature.
Keywords: Global Financial Crisis, 2008-2009.